Weekend versus Weekday Procedures for Total Knee Arthroplasty - Lee, Tiffany; Momtaz, David; Khalafallah, Youssef; Mclennan, Alexandra; Ghali, Abdullah; Ghobrial, Philip; Gonzalez, Roberto; Seifi, Ali; Saleh, Khaled (The Journal of Knee Surgery, 2025)
This study compares the outcomes of elective total knee arthroplasty (TKA) on a weekday versus the weekend. Patients undergoing elective TKA from 2016 to 2020 were identified using the Healthcare Cost and Utilization Project database. Demographics and hospital-related outcomes including length of stay (LOS), total charges, pain, wound disruption, implant infection, and mortality, were collected. Perioperative outcomes were assessed from each patient's concurrent diagnoses. Multivariable analysis was performed. A total of 586,285 patients who underwent elective TKA were identified, of which 2,199 (0.37%) were performed on the weekend. Patients undergoing weekend TKA were slightly older (68.055 ± 9.882 vs. 66.699 ± 9.454, p < 0.001), and had a statistically significant predilection toward Asians, Hispanics, and Blacks (p < 0.001). No significant difference was present in gender, obesity, or preoperative conditions. Weekend TKA patients had increased odds of prolonged LOS (odds ratio [OR]: 1.154 for LOS ≥3 days, p = 0.002) and higher total charges (OR: 1.328, p < 0.001), along with higher odds of uncontrolled pain (OR: 1.257, p = 0.001) and implant infection (OR: 1.418, p = 0.004). No significant differences in wound disruption or mortality were found. Our findings indicate an association between weekend TKA and increased pain, implant infection, LOS, and cost, validating the presence of a weekend effect on TKA. Future research is needed to clarify the underlying causes of this association and feasible ways to mitigate its impact.
Keywords: total knee arthroplasty; elective arthroplasty; weekend effect; day of surgery; postoperative complications